Moderation of The Rupiah Exchange Rate on The Influence of Sharia Stock and Inflation on Economic Growth in IDX-MES Companies 17 - Utami, Tri; Sutiadi, Arif (Universitas Pamulang, 2023)
The welfare of a country can be seen from the level of economic growth. This study aims to determine what factors can affect economic growth in Indonesia with independent variables, namely Sharia stocks and inflation and the rupiah exchange rate as moderation variables. This study used a quantitative descriptive method using secondary data obtained from the annual financial statements of State-Owned Enterprises registered in IDX-MES BUMN 17 of 2016-2020. The result of this study is that partially Sharia Stocks do not affect Economic Growth, but inflation affects Economic Growth; simultaneously, Sharia Stocks and Inflation affect Economic Growth. The Rupiah Exchange Rate cannot moderate the effect of Sharia stocks on economic growth. However, the rupiah exchange rate variable can strengthen the influence of Sharia stocks on economic growth. The Rupiah Exchange Rate can moderate the effect of Inflation on Economic Growth, and the rupiah exchange rate variable can strengthen the effect of inflation on economic growth. The coefficient of determination has a value of 98.77%. It shows the degree of influence given by the independent variable on the solid dependent variable, and the remaining 1.23% can be explained by other independent variables that are not contained in this study.